Performance prediction of inertial auto-reinforce magnetic flywheel energy storage device using finite element magnetic modeling - Akbar, A.R. (Trans Tech Publications Ltd, 2014)
A new feature for flywheel energy storage device is proposed considering the deficiencies in former technology. This feature is introduced as auto-reinforce performance which means giving-back the kinetic energy for flywheel after speed-down occurred (as result of sudden loading). Auto-reinforce performance is an ability to recover the kinetic rotational energy which significantly keeps longer the stored energy of a flywheel device. This novel concept of flywheel is engineered by installing a number of Permanent Magnets (PM) in certain mounting. Hence, the magnetism configuration such magnetic strength, magnetic energy density, pole direction, geometry, and dimension are influential parameters to the mechanical performance. By practicing Finite Element Magnetic Modeling (FEMM), it is possible to predict some designed mechanical parameters such magnetic force and magnetic torque. Finally by evaluating these mechanical parameters, the key performance of this device such as percentage of energy reinforcement and percentage of discharge elongation can be predicted. The main ideas of this paper are: 1) presenting the development stages especially in design prediction using Finite Element Analysis (FEA) software; and 2) discovering the correlation of designed magnetic properties and mechanical parameters for prototyping references. Â© (2014) Trans Tech Publications, Switzerland.